Electrical resistivity of ZnO-Al/PP composites / Shahida Ishak ... [et al.] - Ishak, Shahida; Shamsudin, Siti Hajar; Haliah, Nor Hafidah; Mohd Radzi, Hazwani; Safian, Suhaida Dila; Mahmud, Shahrom (2017)
This study focuses on the electrical resistivity of Zinc oxide - Aluminum/ Polypropylene (ZnO-Al/PP) composites. ZnO-Al/PP composites with ZnO and Al being a filler varied from 0 to 55% of volume were prepared using Laboratory Roll Mill Heater. The composites were subjected to the characterization using non-destructive methods, which are scanning electron microscopy (SEM-EDX) and X-ray diffraction (XRD) techniques. The outcome from the XRD and SEM-EDX has been attained and thus gives an idea about the presence of ZnO and Al particles in PP composites. The electrical resistivity of the composites was investigated by measuring the current and voltage using CV-IV Measurement System, which describes the conductivity property of the composites.